2018
DOI: 10.3390/su10114094
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Ecotoxic Impacts Stemming from Emissions of Cd, Cu, Ni, Pb and Zn from Manure: A Spatially Differentiated Assessment in Europe

Abstract: Metallic elements present in livestock manure as co-contaminants have the potential to cause terrestrial ecotoxic impacts when the manure is used as fertilizer on agricultural soils. The magnitude of this impact at country scale in Europe has, to date, not been quantified. Here, we address this knowledge gap by combining recently developed national emission inventories of Cd, Cu, Ni, Pb and Zn releases from manure with metal- and soil-specific comparative toxicity potentials (CTP) calculated for cropland grid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Plants, due to being sessile and directly dependent on the soil, frequently experience the harmful effects of these heavy metals [5]. Among the heavy metals, cadmium is a highly toxic, non-degradable pollutant that significantly impacts living organisms [6][7][8]. It is discharged into the environment from metalworking industries, power stations, heating systems, and urban traffic [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…Plants, due to being sessile and directly dependent on the soil, frequently experience the harmful effects of these heavy metals [5]. Among the heavy metals, cadmium is a highly toxic, non-degradable pollutant that significantly impacts living organisms [6][7][8]. It is discharged into the environment from metalworking industries, power stations, heating systems, and urban traffic [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…The method is included in the new LCIA methodology LC-IMPACT (LC-IMPACT -A Spatially Differentiated Life Cycle Impact Assessment Method Home Page, 2019). It has been used in two LCA studies so far and Sydow et al (2018)). For comparisons, IMPACT 2002+ and ReCiPe 2008 were chosen because these methods do not consider speciation, cover relatively large number of metallic elements, and are widely used by LCA practitioners (Hauschild et al, 2013;Rosenbaum et al, 2018).…”
Section: Selection Of Life Cycle Impact Assessment Methodsmentioning
confidence: 99%
“…Accordingly, Owsianiak et al (2015) recommended incorporating the emission source effect, including the OW-related emission source effect, in the CTP calculation to improve assessment of the terrestrial ecotoxicological impact of trace elements in LCA procedures. Sydow et al (2018) combined the national inventories performed by Leclerc and Laurent (2017) and the assessment of the terrestrial ecotoxicological impact of OW-related emission sources suggested by Owsianiak et al (2015) to assess the terrestrial ecotoxicological impact of agricultural OW-bound trace element inputs after spreading on agricultural fields in Europe on a country scale. Trace element and country-specific impact scores were calculated from the product of the total mass of a trace element emitted from OW applied on agricultural land in a given country (mtotal) and the areaweighted comparative toxicity potential (CTP) for the trace element and the target country.…”
Section: Ecotoxicity Of Ow-borne Trace Elementsmentioning
confidence: 99%
“…Despite this marked variability in grid-specific CTP, the country-specific impact scores were closely correlated with mtotal rather than with the area-weighted CTP. Sydow et al (2018) attributed the relatively small effect of CTP on the impact scores to the area weighting of grid-specific CTP at the country scale, suggesting that OW, and hence trace elements, are homogeneously applied on agricultural surface areas.…”
Section: Ecotoxicity Of Ow-borne Trace Elementsmentioning
confidence: 99%